Hubungan Komorbiditas Terhadap Mortalitas Pasien COVID-19 Di Rumah Sakit Pertamina Jaya Jakarta Pusat - Siti Nurhayati; Ida Safitri Laksanawati; Rizaldi Taslim Pinzon (Majalah Kedokteran Indonesia, 2024)
Introduction: The COVID-19 pandemic is a disease outbreak caused by SARS-CoV-2; as of July 20, 2021, there were 2,950,058 positive cases and 76,200 deaths in Indonesia. COVID-19 patients with comorbidities are mostly hypertension (50%), diabetes mellitus (37.2%), and heart disease (16.7%). This study aims to prove how comorbidities affect the mortality of COVID-19 patients at Pertamina Jaya Hospital, Central Jakarta.Method: This study is a retrospective cohort analysis. The sample comprised 500 patients, 250 comorbid groups, and 250 without comorbidities. The secondary data source is medical records of COVID-19 patients at Pertamina Jaya Hospital from April 2020 to September 2021. Data analysis using univariate, bivariate, and multivariate.Result: Multivariate analysis with logistic regression resulted in a value of (32.197 95% CI 9.714 - 106.718) so that there is an influence on the risk of death with a comorbid history in COVID-19 patients. The relative risk value proves that hypertension has a 3-fold risk of death (3.124 95% CI 1.441 - 6.773), diabetes mellitus is 2.5 times (2.521 95% CI 1.055 - 6.024), while heart disease is 2.3 times (2.325 95% CI 1.169 - 4.622).Conclusion: Hypertension, diabetes mellitus, and heart disease are comorbidities that are predictors of mortality for COVID-19 patients due to a higher risk of death.